The impact of scleral contact lenses correction of keratoconus on wave-front and accommodation parameters - E. P. Tarutta; A. T. Khandzhyan; N. A. Tarasova; S. G. Harutyunyan; O. V. Guryanova; A. V. Ivanova (Российский офтальмологический журнал, 2022)
Purpose: to evaluate the wave-front and accommodation changes in various stages of keratoconus corrected by scleral contact lenses.Material and methods. 20 patients (39 eyes) aged 18–37 with keratoconus of various stages (8 eyes with stage I, 3 eyes with stage II, 12 eyes stage II/III and 16 eyes with stage III wore OneFit or OneFitMed scleral lenses, made of hard gas-permeable material Contamac (Great Britain) with Dk 100 and mean thickness of 200–220 μm. All patients were examined using refractometry before and after cycloplegia, tested for uncorrected and best corrected visual acuity, relative accommodation reserve (RAR), binocular and monocular accommodation response (with Grand Seiko Binocular Open Field Autorefkeratometer WR-5100K, Japan) for full spectacle correction and scleral contact lens correction. 17 patients (34 eyes) were tested for corneal aberrations with OPD Scan III aberrometer (Nidek) without correction and with scleral contact lenses.Results. Patients with keratoconus demonstrated a manifest form of refraction -5.26 ± 0.45 D (by sphere equivalent) and a cycloplegic refraction of -4.75 ± 0.33 D. Uncorrected visual acuity averaged 0.26 ± 0.05, increasing with full spectacled correction to 0.54 ± 0.07 and with scleral contact lenses correction to 0.95 ± 0.08. Keratoconus patients demonstrated binocular accommodative response (BAR) of +4.5 to -6.12 D averaging -1.43 ± 0.34 D with full spectacled correction diopters and of -0.5 to -8.13 D averaging - 2.83 ± 0.23 D with scleral contact lenses, р ≤ 0.01. We could not measure the BAR in 3 patients with keratoconus stage III. Monocular accommodative response (MAR)with a full correction with glasses averaged -0.98 ± 0.33 D (from + 6.0 to -5.0 D) with full spectacled correction and -2.41 ± 0.27 D (from +1.25 to -5.5 D) with scleral contact lenses, р ≤ 0.02. At the same time monocular accommodative response of 4 patients with keratoconus of the third stage of disease was not available to assess. So, accommodative response significant increased with scleral contact lenses. Positive relative accommodation with a full correction with glasses averaged 1.50 ± 0.35 D, with scleral contact lenses – 2.25 ± 0.29 D, р ≤ 0.01. The level of all aberrations, from lower to higher orders was significantly increased. With scleral contact lenses that correct the shape of the anterior surface of the cornea, the level of all corneal aberrations dropped to nearly normal values, while the coefficient of asphericity dropped below normal values, and the point spread function parameter (PSF) increased by fifteen times (to reach 0.06).Conclusions. Patients with keratoconus demonstrated a generally lower objective accommodative response as compared to normal values, but with the scleral lenses it increases to the normal level. Scleral contact lenses normalize corneal aberrations and increase the quality of vision. All of the above justifies the recommendation to use scleral contact lenses for optical correction of keratoconus to increase the vision, the accommodation response and visual comfort, including that of near-visual work.